595 Managerial role as a risk factor of problem drinking verified by audit. (24th April 2018) - Inoue, Daisuke; Tanaka, Hiroshi; Tomonaga, Taisuke; Horie, Seichi
Abstract : Introduction: In Japan, people scoring 8 to 14 points by the Alcohol Use Disorder Identification Test (AUDIT) are recommended to receive the health guidance to avoid risk of alcoholism and those scoring 15 or higher are considered to need the specialised medical treatment of their problem drinking. There are many risk factors of alcohol related disorders among workers such as a managerial role, a shift work, smoking (Brinkman index 400 or more) and the result of the alcohol patch test; however, they have not been verified by the scores of AUDIT. Methods: We conducted a survey using a self-administered questionnaire including AUDIT among 2915 employees of a manufacturing worksite who received a periodic medical examination in fiscal 2015. We used binomial logistic regression analysis to explore the risk factors to predict development of the condition scoring 15+points by AUDIT among various independent variables: age, managerial position, shift work, smoking, the result of the alcohol patch test to screen variant aldehyde dehydrogenase. Statistically significant level was set at p<0.05. Result: We analysed the data obtained from 2299 male employees under 60-year-old who answered to all questions, and found 183 workers (8.0%) scored 15+points by AUDIT. The significantly increased risks were found with managerial roles (OR: 1.74), with negative result of the alcohol patch tests (OR: 6.87) and with smoking habit (OR: 1.71); however, the significant relationship was not found with shift work. Discussion: Our result may reflect the tendency that managers are likely to excuse their drinking habit as a means of business practice and communication, and people with high social standing can afford to drink. There may be a synergistic effect between drinking and smoking. Occupational health should be more cautious to prevent problem drinking based on personal and social characteristics.